A Systematic Literature Review of Augmented Reality–Oriented Professional Development Programs for Teachers - Sahesenem Oz; Bahadır Namdar; Tuğba Yüksel; Ibrahim Delen; Gökhan İnce (Scientia Publica Media, 2026)
Augmented Reality (AR) combines real-world experiences with virtual elements and offers various positive educational outcomes. However, one obstacle hindering AR’s use in education is teachers’ limited pedagogical knowledge regarding the instructional implementation of AR in teaching. Supporting teachers with professional development programmes to integrate this novel technology into education is salient. Thus, this study analysed 17 professional development programmes focused on integrating AR into teaching. For this purpose, a framework was applied to examine dimensions that make training effective, including the type of activity (traditional and reform), duration, collective participation, content focus (theoretical, pedagogical and practical knowledge), active learning (e.g., observing teaching, planning classroom implementation, reviewing student work, and presenting, leading, and writing), and coherence (e.g., connections with goals, alignment with state and district standards and assessments). Findings from the systematic analysis indicated that the majority of teacher professional development programmes addressed theoretical, pedagogical, and practical knowledge. However, observation of teaching and review of students’ work in active learning dimensions were lacking. Regarding the general characteristics of studies, most employed a mixed-method approach and delivered the programme in person. Marker-based augmented reality was the most preferred type, and smartphones and tablets were the most commonly used electronic devices. The findings can be beneficial for AR-oriented professional development studies by presenting an overview of effective professional development programme dimensions. Nonetheless, there is still a need for effective AR-oriented professional development programmes for pre- and in-service teachers, and this review can assist in developing new teacher professional development programmes focusing on AR.